STUDI TENTANG ISIM MUSYTAQ - Ali Asrun Lubis (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2014)
Isim Musytaq  is  “Isim  is take from  fi‟il”,  it means that, noun originated from verb, like “read become reader”. In Arabic language obtain some words that contain from  isim musytaq,  like  isim masdar, isim fa‟li, isim maf‟ul and soon. Isim Musytaq has  i‟rab  like the other  isim  that appropriate with the place and position where this word is put. It can be as  isim marfu‟, isim mansub  and  isim  that is  majrur.  In this case,  Isim Musytaq  can be Mudzakkar or Muannats, same with Mufrad, Mutsanna and Jamak.